Substrate potential of last interglacial to Holocene permafrost organic matter for future microbial greenhouse gas production. - Mangelsdorf, Kai; Stapel, Janina Gabriele (PANGAEA, 2018)
Within the Russian-German research project CARBOPERM the organic matter (OM) in several permafrost cores from Bol'shoy Lyakhovsky Island in NE Siberia was investigated. In the context of the observed global warming the aim was to evaluate the potential of freeze-locked OM from different depositional ages (Eemian to Holocene) to act as a substrate provider for microbial production of greenhouse gases from thawing permafrost. To assess this potential bulk elemental parameters (total carbon (TC), total organic carbon (TOC), total inorganic carbon (TIC), total nitrogen (TN), TOC/TN ratios, Hydrogen Index and Oxygen Index data), the concentrations of free (directly extractable part) and bound (after ester cleavage) formate and acetate, the concentration of phospholipid life markers and the concentration of branched and isoprenoid glycerol dialkyl glycerol tetraethers (GDGT) were determined.
Bulk parameter data, formate and acetate data and microbial life and past biomarkers from Eemian to Holocene permafrost core material drilled on Bol'shoy Lyakhovsky Island (Siberia) within the CarboPerm project
Keywords: 2,3-di-O-phytanyl-sn-glycerol; Acetate; Bolshoy-Lyakhovsky_Island_2014; Bolshoy Lyakhovsky Island, East Siberia, Russia; Branched and isoprenoid tetraether index; Branched glycerol dialkyl glycerol tetraether, Ia; Branched glycerol dialkyl glycerol tetraether, Ib; Branched glycerol dialkyl glycerol tetraether, II group; Branched glycerol dialkyl glycerol tetraether, III group; Carbon, inorganic, total; Carbon, organic, total; Carbon, organic, total/Nitrogen, total ratio; Carbon, total; CARBOPERM; Crenarchaeol; DEPTH, sediment/rock; Formate; Formation, turnover and release of carbon in Siberian permafrost landscapes; GeoForschungszentrum Potsdam; GFZ; Hydrogen index, mass HC per unit mass total organic carbon; Identification; Isoprenoid acyclic glycerol dialkyl glycerol tetraether; Isoprenoid dicyclic glycerol dialkyl glycerol tetraether; Isoprenoid monocyclic glycerol dialkyl glycerol tetraether; L14-02; L14-03; L14-04; L14-05; LAND; Nitrogen, total; Oxygen index, mass HC per unit mass total organic carbon; Phospholipid fatty acids; Sample ID; Sampling/measurement on land; Sampling on land